Peran Mediasi dalam Penyelesaian Sengketa Wanprestasi Sewa Menyewa - Kalila, Sheza Vanisha; Rahmah, Siti Marsha Zahida; Hardiyanti, Talitha Kirana; Azzahra, Shadrina Ghaisani; Gultom, Elisatris (Universitas Pahlawan Tuanku Tambusai, 2025)
Mediation serves as a crucial mechanism in resolving breach of contract disputes by providing an alternative to litigation that emphasizes collaboration and mutual agreement. This study investigates the role and effectiveness of mediation in addressing disputes arising from contractual non-performance. Employing a qualitative approach, the research examines case studies and legal frameworks governing mediation in contract disputes. The findings reveal that mediation offers several advantages over litigation, including reduced costs, faster resolution times, and the preservation of business relationships. These benefits make mediation a preferred choice, especially for parties seeking to maintain ongoing partnerships. The study also highlights the role of mediators as impartial facilitators who guide parties toward creative and mutually beneficial solutions. Mediators assist in clarifying issues, addressing misunderstandings, and fostering open communication, which are essential in resolving complex contractual disputes. However, the success of mediation is contingent upon the willingness of both parties to engage in the process and their commitment to finding a resolution. This paper underscores the significance of promoting mediation as a primary dispute resolution method in breach of contract cases. It advocates for strengthening legal frameworks and increasing public awareness to enhance its accessibility and effectiveness. By doing so, mediation can be further integrated into the legal landscape, offering an efficient and harmonious approach to resolving disputes while alleviating the burden on courts.